2020
DOI: 10.31372/20200503.1106
|View full text |Cite
|
Sign up to set email alerts
|

Change in Body Weight and Serum Albumin Levels in Febrile Neutropenic Lung Cancer Patients

Abstract: Although advances have been made in the treatment and prevention of febrile neutropenia (FN) in cancer patients treated with chemotherapy, it is still a complication that requires clinical attention. Impaired nutritional status in patients who develop FN can affect the continuation of cancer treatment, but it has not been investigated. We conducted a retrospective longitudinal study in order to clarify (1) if body weight and serum albumin levels change in lung cancer patients who do and do not develop FN, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Our results for LAHNSCC were partially consistent with those of previous reports on other malignancies [139][140][141][142][143]. Patients with esophageal cancer receiving CCRT who exhibited increased albumin levels during the treatment course had better survival outcomes [139,143].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results for LAHNSCC were partially consistent with those of previous reports on other malignancies [139][140][141][142][143]. Patients with esophageal cancer receiving CCRT who exhibited increased albumin levels during the treatment course had better survival outcomes [139,143].…”
Section: Discussionsupporting
confidence: 91%
“…Patients with esophageal cancer receiving CCRT who exhibited increased albumin levels during the treatment course had better survival outcomes [139,143]. Kayauchi et al analyzed 226 patients with lung cancer undergoing cytotoxic chemotherapy, and reported that patients with decreased albumin levels during treatment significantly suffered from febrile neutropenia toxicity [141]. The histidine degradation pathway is essential for determining the chemosensitivity of tumor cells to methotrexate; thus, the addition of histidine to methotrexate significantly reduces tumor growth in animal models [140].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of FN may decrease due to the therapeutic impact of G-CSF therapy. 12 The retrospective study revealed an incidence of 58.3% for neutropenia and 8.3% for FN in advanced NSCLC patients undergoing platinum-based chemotherapy doublets. 13 Fujiwara et al research showed the incidence of FN was 20% in lung cancer patients in Japan who had never received chemotherapy while receiving etoposide and platinum in combination.…”
Section: Incidencementioning
confidence: 99%